REKOMENDASI TATA KELOLA TEKNLOGI INFORMASI MENGGUNAKAN COBIT 2019 DI KAMPUS XYZ - Sangka, Yuliana; Indrayani, Lilis (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
With the development of Information Technology, learning activities and the world have also changed. Every educational institution requires good governance in order to achieve the expected goals. Campus responsible for the use of Information Technology so that when damage occurs it is not handled properly and there is a risk of data security breaches and compliance with regulations which could be detrimental to the XYZ Campus. The aim of this research is to provide recommendations in the form of IT governance design using COBIT 2019 to help XYZ campus implement the prioritized programs contained in the RENSTRA document. Data was obtained through interviews and questionnaires. The interview results show that the prioritized process domains are: EDM01, EDM03, EDM04, APO04, APO07, BAI05, BAI09, MEA04. Data analysis shows that the current IT process capability level is still on average at level 1, while the expected average is level 3 and 4, meaning that XYZ campus has not yet carried out most of the existing IT process activities so it requires a better IT governance design. appropriate to be used as a reference in realizing prioritized programs